The theological vindication of resistance against enforced motherhood - Nickel, Mary (Body and religion, 2022)
For the suffragists of the 19th century, women’s enfranchisement was a central goal. Yet the right to vote was not nearly as vital to the suffragists as the right to one’s own bodily freedom. Furthermore, as they saw it, bodily autonomy was a ‘sacred’ right: it was grounded theologically. Most concerning to the suffragists were the ways in which women of their time were forced against their will to become mothers. This article presents the suffragists’ theological grounds for resisting enforced motherhood. As I argue, doing so serves three purposes. First, it helps pro-choice Christians understand the ways in which their faith might support the defense of abortion access. Second, it foregrounds the political theological insights of the all too often overlooked suffragists. Finally, and perhaps most importantly, it gives the lie to a widespread mischaracterization of the suffragists as would-be advocates of the contemporary anti-abortion movement.